Effects of low dose radiation on immune cells subsets and cytokines in mice. Issue 3 (11th May 2020) - Liu, Xiaochang; Liu, Zheng; Wang, Duo; Han, Yang; Hu, Sai; Xie, Ying; Liu, Yike; Zhu, Maoxiang; Guan, Hua; Gu, Yongqing; Zhou, Ping-Kun
Abstract: Whole-body exposure to low-dose radiation due to diagnostic imaging procedures, occupational hazards and radiation accidents is a source of concern. In this study, we analyzed the effects of single and long-term low-dose irradiation on the immune system. Male Balb/c mice received a single whole-body dose of irradiation (0.01, 0.05, 0.2, 0.5 or 1 Gy). For long-term irradiation, mice were irradiated 10 times (total dose of 0.2, 0.5 or 1 Gy) over a period of 6 weeks. Two days after single or long-term irradiation, the numbers of splenic macrophages, natural killer cells and dendritic cells were reduced, and the spleen organ coefficient was decreased. At 2 Days after long-term low-dose irradiation, the number of white blood cells in the peripheral blood of the mice decreased. Between 7 and 14 Days after long-term low-dose irradiation, the number of immune cells in the thymus and spleen began to increase and then stabilized. Th1/Th2 cytokines and reactive oxygen species-related proteins first decreased and then increased to a plateau. Our results show a significant difference in the effects of single and long-term low-dose irradiation on the immune system.